ZEROING IN ON RED CELL UNIT EXPIRY DUE TO AGE. (February 2015) - Ayyalil, Fathima M.; Irwin, Greg; Manolis, Michael; Martens, Vicki; Seldon, Michael; Deveridge, Sandra; Enjeti, Anoop K.
Abstract : National Blood Authority identifies age related expiry of red cell units as a significant contributor to wastage of precious voluntary donations. Policy changes to reduce age related wastage can result in significant cost savings and improved inventory management. Aim: To evaluate effectiveness of policy (pilot National Inventory Management Framework report) changes to achieve zero wastage of red cell units expiring due to age. Methods: Retrospective analysis of age related red cell wastage in Hunter New England Health Service during 12 months preceding and after policy changes implemented since November 2013. Results: 1. Inventory levels for red cells decreased by 30.1%. 2. Policy involving age limit (16–28 days) for accepting red cells resulted in 0–2.5% of total red cells received in the main laboratory from peripheral hospitals being older than 28 days, compared to 6–41% previously. 3. Policy changes resulted in zero wastage due to age over last 12 months, while age contributed to 17.8–69.4% of total wastage previously. Total red cell transfusions remained constant. 4. There was no increase in use of emergency couriers. Discussion: Key factors for significant reduction in age related wastage were reduction in inventory levels, stock rearrangement and regulations for returning blood products from peripheral hospitals.